A Ricardo-Sraffa Paradigm Comparing Gains from Trade in Inputs and Finished Goods - Samuelson, Paul A (Journal of Economic Literature, 2001)
Here is how the 1817 Ricardo comparative advantage trade benefit analysis has to be modified to take account of post-1960 Sraffian benefits from capital-using technologies. By bringing J. S. Mill's demand model up to date in terms of its implicit geometric-mean money-metric utility, specific measurements for real net national product are calculated to partition sources of welfare gains (from output enhancements and taste-preference accommodations) in scenarios of (1) trade between equals, (2) trade between poor and rich nations, and (3) for biased inventions that enable a poor country to take over production of items in which formerly the rich place enjoyed comparative advantage. History of economic doctrine is mined to advance today's frontier of scientific knowledge—a forward-looking function for “Whig history.”